Understanding Student Teachers' Behavioural Intention to Use Technology: Technology Acceptance Model (TAM) Validation and Testing - Wong, Kung-Teck; Osman, Rosma bt; Goh, Pauline Swee Choo; Rahmat, Mohd Khairezan (2013)
This study sets out to validate and test the Technology Acceptance Model (TAM) in the context of Malaysian student teachers' integration of their technology in teaching and learning. To establish factorial validity, data collected from 302 respondents were tested against the TAM using confirmatory factor analysis (CFA), and structural equation modelling (SEM) was used for model comparison and hypotheses testing. The goodness-of-fit test of the analysis shows partial support of the applicability of the TAM in a Malaysian context. Overall, the TAM accounted for 37.3% of the variance in intention to use technology among student teachers and of the five hypotheses formulated, four are supported. Perceived usefulness is a significant influence on attitude towards computer use and behavioural intention. Perceived ease of use significantly influences perceived usefulness, and finally, behavioural intention is found to be influenced by attitude towards computer use. The findings of this research contribute to the literature by validating the TAM in the Malaysian context and provide several prominent implications for the research and practice of technology integration development. Appendix 1 presents "Constructs and corresponding items." (Contains 6 tables and 3 figures.)